2020
DOI: 10.3892/etm.2020.8672
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of LYN in human gastric cancer via the Wnt/β‑catenin and AKT/mTOR pathways

Abstract: ���� ������ ����l�, w���� pl��� �� ��p������ ��l� �� �ul��pl� �u���-��l���d �u�������. T�� �u����� ��ud� d����������d ���� L�N �u������� �� � p��-����g��� �� AG� g������ ������ ��ll�. It was found that LYN expression levels were significantly raised in gastric cancer tissue and were significantly associated w��� ��� p����l�g���l g��d�� �� p������� w��� g������ ������. T��� w�� �����pl����d �� �������g d�w� L�N �� AG� ��ll� u���g ����� ����p�� RNA ���RNA� pl����d ������������, w��� ��v���� ��������p����-qu�����… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Lyn is a member of the Src tyrosine kinase family and functions as a proto-oncogene in tumor progression. Lyn is frequently overexpressed in numerous tumor types, including chronic myelogenous leukemia, renal cancer, cervical cancer, head and neck squamous cell carcinoma, gastric cancer, and prostate cancer [ 38 ]. High expression of Mybl2 and Lyn may be associated with the characteristics of iF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lyn is a member of the Src tyrosine kinase family and functions as a proto-oncogene in tumor progression. Lyn is frequently overexpressed in numerous tumor types, including chronic myelogenous leukemia, renal cancer, cervical cancer, head and neck squamous cell carcinoma, gastric cancer, and prostate cancer [ 38 ]. High expression of Mybl2 and Lyn may be associated with the characteristics of iF cells.…”
Section: Discussionmentioning
confidence: 99%
“…LYN activation sensitizes insulin receptors [ 132 , 133 ], and increases glucose transport [ 128 , 134 ]. LYN is an important player in multiple tumor-related functions [ 135 ] and is upregulated in cervical cancers [ 136 ], prostate cancers [ 137 ], colon cancer [ 135 ], and Ewing’s sarcoma [ 138 ]. Further, LYN expression predicts poor prognoses for renal cancer patients [ 139 ], head and neck squamous cell carcinoma patients [ 140 ], nonsmall cell lung cancer patients [ 141 ], and breast cancer patients [ 142 ].…”
Section: Lck/yes-related Novel Kinase (Lyn)mentioning
confidence: 99%
“…ABL2 inhibition decreases CXCL12/CXCR4-induced cancer cell invasion [ 91 ]. LYN inhibition increases cancer cell apoptosis, and reduces cancer cell proliferation, migration, and invasion, likely by inactivating the WNT/Beta-Catenin and AKT/mTOR pathways and activating the mitochondrial apoptotic pathway [ 135 ]. FYN inhibition decreases migration and invasion, possibly via STAT3 signaling [ 255 ].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwarz et al showed that LYNactivating mutations were associated with antiestrogen resistance for breast cancer patients with estrogen receptorpositive (37). LYN also acted as the tumor driver in gastric cancer cells via activation of the mitochondrial apoptotic pathway and inhibition of the Wnt/β-catenin and AKT/mTOR pathways (38). LCK was detectable in multiple cancer types, including breast cancer (39), colon cancer (40), and lung carcinoma (41).…”
mentioning
confidence: 99%